GADHON SALIN SWARA: INTERPRETASI GAMELAN GADHON - Hanan, Laurentius; Pambayun, Wahyu Thoyyib (Institut Seni Indonesia Surakarta, 2023)
This article recounts the author's experience in the process of composing